Effects of aquosus extracts of the weeds Cyperus rotundus L. (Cyperaceae) Cyperus rotundus L . ( C y p e r a c e a e ) Cyperus rotundus on seeds germination and growth of seedlings of corn ( Zea mays L.) cv. Pioneer 3031 - Laynez Garsaball, José A. (2007)
The objective of this experiment was to determine the effects of foliage water extracts of purple nutsedge ( Cyperus rotundus L.) on seed germination and seedling growth of corn ( Cyperus rotundus L . ) o n s e e d g e r m i n a t i o n a n d s e e d l i n g g r o w t h o f c o r n ( Cyperus rotundus Zea mays L.) cv. Pioneer 3031. An extract was prepared with nutsedge foliage of 15 days at 15% w/v and for dilution, extracts of 2, 4 and 6% w/v were prepared, pH and electric conductivity (S.cm -1 ) were determined. Distilled water was uses as a control. Twenty seeds were sowed in a double layer of absorbent paper on trays, covered with two leaves of absorbent paper and they were watered three times per day using foliage extracts. A randomized complete block design was used with four extract concentrations (0, 2, 4 y 6% w/v) and fi ve replications. The traits were determined twelve days after sowing. An analysis of variance and regression were applied. The pH diminished and the electrical conductivity increased when concentration of extract increased. The germination, seedling height, radicle length, dry shoot weight and the relationship dry shoot weight/dry radicle weight decreased proportionally with increased extract concentration, contrarily, dry radicle weight was increased. Relationship seedling height/radicle length was not affected by the extracts.